Web-Based Madrasah E-Report Information System at Madrasah Ibtida'iyah Salafiyah Syafi'iyah Putra - Abdullah Amjad Bawazin; Achmad Baijuri; Firman Santoso (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Before this study, Madrasah Ibtida’iyah Salafiyah Syafi’iyah (MISS) Putra managed student assessment data in Microsoft Excel and prepared report cards using the mail merge feature in Microsoft Word. This workflow distributed academic records across multiple files, increasing the risk of data inconsistencies, data-entry errors, duplication, and delays in report card preparation. This study aimed to design and implement a web-based e-report information system that centralizes academic data management and supports grade processing, report card generation, and access to academic information at MISS Putra. The system was developed using the Waterfall model, comprising requirements analysis, system design, implementation, testing, deployment, and maintenance. The application was built with the Laravel framework, PHP, and MySQL. Functional testing was conducted using the black-box method on five core functions: user login, student data management, grade entry, report card generation, and report card printing. The test results showed that all five functions produced the expected outputs. The implemented system centralizes academic records, reduces repeated data entry, and supports more practical access to academic information for administrators, teachers, homeroom teachers, madrasah leaders, and student guardians.